Thermodynamic analysis of DNA binding by a Bacillus single stranded DNA binding protein - Biswas-Fiss, Esther E (BioMed Central, 2012)
BACKGROUND: Single-stranded DNA binding proteins (SSB) are essential for DNA replication, repair, and recombination in all organisms. SSB works in concert with a variety of DNA metabolizing enzymes such as DNA polymerase. RESULTS: We have cloned and purified SSB from Bacillus anthracis (SSB(BA)). In the absence of DNA, at concentrations ≤100 μg/ml, SSB(BA) did not form a stable tetramer and appeared to resemble bacteriophage T4 gene 32 protein. Fluorescence anisotropy studies demonstrated that SSB(BA) bound ssDNA with high affinity comparable to other prokaryotic SSBs. Thermodynamic analysis indicated both hydrophobic and ionic contributions to ssDNA binding. FRET analysis of oligo(dT)(70) binding suggested that SSB(BA) forms a tetrameric assembly upon ssDNA binding. This report provides evidence of a bacterial SSB that utilizes a novel mechanism for DNA binding through the formation of a transient tetrameric structure. CONCLUSIONS: Unlike other prokaryotic SSB proteins, SSB(BA) from Bacillus anthracis appeared to be monomeric at concentrations ≤100 μg/ml as determined by SE-HPLC. SSB(BA) retained its ability to bind ssDNA with very high affinity, comparable to SSB proteins which are tetrameric. In the presence of a long ssDNA template, SSB(BA) appears to form a transient tetrameric structure. Its unique structure appears to be due to the cumulative effect of multiple key amino acid changes in its sequence during evolution, leading to perturbation of stable dimer and tetramer formation. The structural features of SSB(BA) could promote facile assembly and disassembly of the protein-DNA complex required in processes such as DNA replication.